Examining the Impact of Fluctuations in Exchange Rates on the Balance of Trade: Does the Marshall-Lerner Condition and J-Curve Theory Hold for Botswana? - Tiro, Lakidzane G. M.; Chiwira, Oscar (International Journal of Economics and Financial Issues, 2025)
The study examined the influence of real exchange rates fluctuations on the trade balance in Botswana. The main objectives were to assess the effects of real exchange rates on the trade balance and determine whether the Marshall – Lerner condition and the J-curve theory hold for Botswana using quarterly time series data from 1995 to 2022. The Johansen Cointegration and Vector Error Correction Model (VECM) were used to assess the impact of real exchange rates on the trade balance. The findings suggest that real exchange rates have a negative impact on the trade balance in the long run, indicating that the Marshall – Lerner condition is not valid. This implies that a weakening of the Botswana Pula does not affect the country’s net exports. In the short run, the coefficient of the real exchange rate was negative but statistically insignificant, indicating the absence of the J-curve effect. This indicates that Botswana’s net exports performance is not affected by the devaluation of the domestic currency. The study recommends that currency misalignment should be avoided. Furthermore, the study's findings revealed that real exchange rates affect the trade balance in both the short run and long run; therefore policy makers should maintain the current monetary and managed float exchange rate policies.